IMPLEMENTASI PROGRAM PENGEMBANGAN PROFESIONAL GURU MELALUI LESSON STUDY DI SEKOLAH DASAR NEGERI - Ulum, Apri Pil Bahrul (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
This study examines the implementation of lesson study in public elementary schools as a model for teacher professional development that is relevant to the Merdeka Curriculum. The objectives of this study are to describe lesson study practices, analyze supporting and inhibiting factors, and assess its impact on teachers' pedagogical competencies. The method used is a literature study by reviewing various national and international studies in the last five years. The results of the study show that lesson study encourages teachers to make more careful planning, structured implementation, and meaningful critical reflection. The main supporting factors include collaboration between teachers and support from the principal, while the obstacles that often arise are time constraints, teacher resistance to open evaluation, and a lack of supporting facilities. The impact of implementation is seen in improved pedagogical competence, the formation of a reflective culture in the school environment, and increased student engagement and learning outcomes. Overall, lesson study has proven to be a simple, inexpensive, yet effective professional development strategy. However, its success is greatly influenced by institutional support and a collaborative culture that enables teachers to work together consistently in designing, implementing, and reflecting on learning. These findings confirm that lesson study can be a sustainable solution for improving the quality of basic education in Indonesia.ABSTRAKPenelitian ini mengkaji implementasi lesson study di sekolah dasar negeri sebagai model pengembangan profesional guru yang relevan dengan Kurikulum Merdeka. Tujuan penelitian adalah mendeskripsikan praktik lesson study, menganalisis faktor pendukung dan penghambat, serta menilai dampaknya terhadap kompetensi pedagogik guru. Metode yang digunakan berupa studi pustaka dengan menelaah berbagai penelitian nasional dan internasional dalam lima tahun terakhir. Hasil kajian menunjukkan bahwa lesson study mendorong guru melakukan perencanaan lebih matang, pelaksanaan terstruktur, serta refleksi kritis yang bermakna. Faktor pendukung utama meliputi kolaborasi antarguru dan dukungan kepala sekolah, sedangkan hambatan yang sering muncul adalah keterbatasan waktu, resistensi guru terhadap evaluasi terbuka, dan kurangnya sarana pendukung. Dampak implementasi terlihat pada peningkatan kompetensi pedagogik, terbentuknya budaya reflektif di lingkungan sekolah, serta meningkatnya keterlibatan dan hasil belajar siswa. Secara keseluruhan, lesson study terbukti sebagai strategi pengembangan profesional yang sederhana, murah, namun efektif. Namun, keberhasilannya sangat dipengaruhi oleh dukungan kelembagaan dan budaya kolaboratif yang memungkinkan guru bekerja sama secara konsisten dalam merancang, melaksanakan, dan merefleksikan pembelajaran. Temuan ini menegaskan bahwa lesson study dapat menjadi solusi berkelanjutan untuk meningkatkan kualitas pendidikan dasar di Indonesia.